Bond engineering of molecular ferroelectrics renders soft and high-performance piezoelectric energy harvesting materials - Hu, Yuzhong (2022)
Piezoelectric materials convert mechanical stress to electrical energy and thus are widely used in energy harvesting and wearable devices. However, in the piezoelectric family, there are two pairs of properties that improving one of them will generally compromises the other, which limits their applications. The first pair is piezoelectric strain and voltage constant, and the second is piezoelectric performance and mechanical softness. Here, we report a molecular bond weakening strategy to mitigate these issues in organic-inorganic hybrid piezoelectrics. By introduction of large-size halide elements, the metal-halide bonds can be effectively weakened, leading to a softening effect on bond strength and reduction in polarization switching barrier. The obtained solid solution C6H5N(CH3)3CdBr2Cl0.75I0.25 exhibits excellent piezoelectric constants (d33 = 367 pm/V, g33 = 3595 × 10-3 Vm/N), energy harvesting property (power density is 11 W/m2), and superior mechanical softness (0.8 GPa), promising this hybrid as high-performance soft piezoelectrics.